Ten Years Assessment of Shifting Cultivation on Land Cover and Carbon Storage in Timor Island, Indonesia - Kusuma, Aprisep Ferdhana (2022)
The practice of shifting cultivation has led to forest degradation and deforestation in the Sisimeni Sanam Forest Area, with Special Purpose (SSFAwSP). Therefore, this study aims to assess land cover and carbon storage changes of the practiced shifting cultivation in SSFAwSP over the last ten years using 2013, 2016, and 2021 Landsat imagery. A hybrid classification approach that combines the forest canopy density model and supervised classification of maximum likelihood was used to create land cover maps to detect changes in forest land cover and carbon storage. The results showed that for ten years, the extent and annual rates of deforestation, forest degradation, forest regrowth, and changes in carbon storage were 662.62 ha (4), 319.18 ha (3), 163.8 ha (1), and -54.51 kilo Ton C (3), respectively. This finding indicated that shifting cultivation contributed only 10 and 1 of total deforestation and forest degradation, respectively © Creative Commons License. All the contents of this journal, except where otherwise noted, is licensed under a Creative Commons Attribution License